Chaos and confusion in DSM-5 diagnosis of Internet Gaming Disorder: Issues, concerns, and recommendations for clarity in the field - Kuss, Daria J. (J Behav Addict, 2017)
BACKGROUND: The umbrella term “Internet addiction” has been criticized for its lack of specificity given the heterogeneity of potentially problematic behaviors that can be engaged in online as well as different underlying etiological mechanisms. This has led to the naming of specific online addictions, the most notable being Internet Gaming Disorder (IGD). METHODS: Using the contemporary literature concerning IGD and cognate topics, issues and concerns relating to the concept of IGD are examined. RESULTS: Internet addiction and IGD are not the same, and distinguishing between the two is conceptually meaningful. Similarly, the diagnosis of IGD as proposed in the appendix of the latest (fifth) edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) remains vague regarding whether or not games need to be engaged in online, stating that IGD typically involves specific Internet games, but can also include offline games, adding to the lack of clarity. A number of authors have voiced concerns regarding the viability of including the word “Internet” in IGD, and instead proposed to use the term “video gaming disorder” or simply “gaming disorder,” suggesting addiction to video gaming can also occur offline. CONCLUSION: The DSM-5 has caused more confusion than clarity regarding the disorder, reflected by researchers in the field contesting a supposedly reached consensus for IGD diagnosis.